Dielectric Properties of Sodium Silicate-An Investigation Report - Chakraborty, Sudhangshu; Roy, Kousik; Ayub Sheikh, Md (International Journal of Computer Sciences and Engineering, 2025)
The dielectric properties of sodium silicate (Na2SiO3) (SS) have been investigated in a wide range of frequency and temperatures. A strong dielectric dispersion is found to exist in low-frequency region. The frequency dependent dielectric properties of SS follow universal dynamic response. The measured dielectric data strongly depends on dielectric dispersion and controls the basic relaxation property. However, the parameters that control the dielectric properties such as coupling of ions are found to have frequency and temperature dependency.